PENGARUH REPUTASI KAP, UKURAN KAP, DAN BIAYA AUDIT TERHADAP KUALITAS AUDIT (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2015-2017) - Malinda Rizki; Sudarno Sudarno (Diponegoro Journal of Accounting, 2020)
This research was aimed to examine the influence of audit firm characteristics, including audit firm reputation, audit firm size, and audit fees, on audit quality. The sample of 187 manufacturing companies listed on Indonesia Stock Exchange (IDX) for the period of 2015-2017 was selected by purposive sampling. Data is obtained through company’s financial reports, company’s annual reports and from the database of Pusat Pembinaan Profesi Keuangan The Ministry of Finance of Republic of Indonesia. Data analysis used multiple regression method perform by software IBM SPSS Statistics 22. The result of hypothesis test shows that audit firm reputation are take positive effect toward audit quality. Nevertheless, audit firm size and audit fees are not proven affecting audit quality.